FUNDAMENTAL PRINCIPLES OF THERMODYNAMICS AND THEIR APPLICATIONS IN MODERN SCIENCE (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
This article presents a comprehensive analysis of the fundamental principles of thermodynamics and their extensive applications in modern scientific disciplines. Thermodynamics is a core branch of physics that investigates the relationships between heat, work, energy, and entropy within physical systems. The study systematically examines the four laws of thermodynamics and their implications for energy transformation, equilibrium states, and irreversible processes. In addition, the article highlights the interdisciplinary significance of thermodynamics in contemporary science and technology. Its applications extend to engineering systems such as internal combustion engines, refrigeration and power plants, as well as to biological and medical systems where energy metabolism, cellular respiration, and thermal regulation are critically governed by thermodynamic laws. The research emphasizes that thermodynamic principles provide a universal framework for understanding both macroscopic and microscopic processes in nature.